Potential and viewpoint of smallholders towards pineapple waste management / Siti Nursyazwani Jamaluddin - Jamaluddin, Siti Nursyazwani (Faculty of Plantation and Agrotechnology, 2016)
Waste utilization of fruits and vegetables processing industries are very challenging to handle as it need expertise from the scientists to make a new beneficial product to human. Pineapple waste is mainly from the selection and elimination of components unsuitable for human consumption (Atul,201O). It consists of residual pulp, peels and skin. These wastes can cause environmental pollution problems if not utilized. The purpose of the study is to identify the viewpoints of the smallholders towards the pineapple waste management. To achieve the objectives, a set of data was collected through the questionnaires related to the variables in the study. A sample of 128 respondents among pineapple smallholders in Pontian Johor was collected. The result was analyzed by correlation and regression analysis. From the correlation analysis, the most factors that show clearly the significant is social influence which in moderate correlation followed by price of green product shows to weak correlation. The regression analysis shows social influence factor that significant and most influence to the dependent variable followed by price of green product. So that the study proved that the social influence is the most factors that will make the smallholders realize the importance of the pineapple waste management.